The Concept of Money in the Perspective of Islamic Economics - Sri Artati Salju; Muslimin Kara; Rahmawati Muin (LP2M IAI AL-KHAIRAT PAMEKASSAN, 2026)
Humans have been using money as a tool for transactions for a long time. The money that has been used as the official currency since the time of the Prophet Muhammad and was passed on by the caliphs after him for centuries is the gold dinar and silver dirham. This paper aims to lay out the concept of money according to Islamic economics. For this purpose, the normative legal study method is used in its writing. Among the findings of this study is that in the perspective of Islamic economics, money is everything that is generally accepted and issued by an authorized financial institution as a medium of exchange and a measure and store of value. In addition, the use of gold dinar and silver dirhams is not a religious obligation, but history proves that the two currencies are very stable and not subject to inflation like paper money. According to the Islamic economic perspective, money has three functions, namely as a medium of exchange, as a unit of calculation or measure of value, and as a store of value if money is made of gold and silver. In the financial sector, Islam has many provisions, such as the use of money as a measuring tool for nisab and zakat rates, dowry, kaffarah, nisab cut off hands for thieves, diyat, and jizyah.